2014
DOI: 10.1179/1743294414y.0000000270
|View full text |Cite
|
Sign up to set email alerts
|

Cold spray coating: review of material systems and future perspectives

Abstract: Cold gas dynamic spray or simply cold spray (CS) is a process in which solid powders are accelerated in a de Laval nozzle toward a substrate. If the impact velocity exceeds a threshold value, particles endure plastic deformation and adhere to the surface. Different materials such as metals, ceramics, composites and polymers can be deposited using CS, creating a wealth of interesting opportunities towards harvesting particular properties. CS is a novel and promising technology to obtain surface coating, offerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
334
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 608 publications
(372 citation statements)
references
References 133 publications
0
334
0
6
Order By: Relevance
“…For a review of successfully cold-sprayed and studied material systems and applications see e.g. [20,[171][172][173][174]. Figure 26 shows a few examples of coldsprayed coatings, as investigated by the authors and co-workers at Helmut Schmidt University.…”
Section: Materials and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a review of successfully cold-sprayed and studied material systems and applications see e.g. [20,[171][172][173][174]. Figure 26 shows a few examples of coldsprayed coatings, as investigated by the authors and co-workers at Helmut Schmidt University.…”
Section: Materials and Applicationsmentioning
confidence: 99%
“…1. Scholarly publications on CS include several books and review articles, covering various aspects of the process and its applications [15][16][17][18][19][20][21][22][23]. The topic is broad and spans over various fields of research, from fluid dynamics to solid mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…However, low ductility materials (e. g. ceramics) are more difficult to deposit [8] since they can rebound when impacting substrate surfaces, resulting in a reduced deposition rate. Thus, brittle materials often need to be combined with more ductile materials for successful cold spraying [9]. It has been found that cold sprayed coating compositions are different to that of simply mixed feedstocks because the deposition efficiencies of the constituent powders are not the same at the same processing parameters [10].…”
Section: Introductionmentioning
confidence: 99%
“…For these metals and their alloys, the thermal properties are not considered, but this property can be important for materials with higher strength, e.g., Fe-, Ni-and Ti-based materials. In these cases, low process temperatures may not be successful in depositing them, since no enough energy is provided, but even thus, deposition of these materials using CS technology has been reported 41 .…”
Section: Influence Of Composition Structure and Size Of The Feedstomentioning
confidence: 99%